Chemical composition of barks from Quercus faginea trees and characterization of their lipophilic and polar extracts - Ferreira, Joana P.A. (2018)
The bark from Quercus faginea mature trees from two sites was chemically characterized for the first time. The barks showed the following composition: ash 14.6%, total extractives 13.2%, suberin 2.9% and lignin 28.2%. The polysaccharides were composed mainly of glucose and xylose (50.3% and 35.1% of all monosaccharides respectively) with 4.8% of uronic acids. The suberin composition was: ω-hydroxyacids 46.3% of total compounds, ɑ,ω-alkanoic diacids 22.3%, alkanoic acids 5.9%, alkanols 6.7% and aromatics 6.9% (ferulic acid 4.0%). Polar extracts (ethanol-water) had a high phenolic content of 630.3 mg of gallic acid equivalents (GAE)/g of extract, condensed tannins 220.7 mg of catechin equivalents (CE)/g extract, and flavonoids 207.7 mg CE/g of extract. The antioxidant activity was very high corresponding to 1567 mg Trolox equivalents/g of extract, and an IC50 of 2.63 μg extract/ml. The lipophilic extracts were constituted mainly by glycerol and its derivatives (12.3% of all compounds), alkanoic acids (27.8%), sterols (11.5%) and triterpenes (17.8%). In view of an integrated valorization, Quercus faginea barks are interesting sources of polar compounds including phenols and polyphenols with possible interesting bioactivities, while the sterols and triterpenes contained in the lipophilic extracts are also valuable bioactive compounds or chemical intermediates for specific high-value market niches, such as cosmetics, pharmaceuticals and biomedicine